Mechanical behavior of grouted sleeve connection for rebars in precast concrete structures and reliability analysis considering the ratio of anchorage length to rebar diameter - Yong Zhao; Haipeng Zhang; Zuanfeng Pan; Guozhen Li (Case Studies in Construction Materials, 2024)
Grouted sleeve connection is the widely used method for the connection of stressed steel reinforcement bars in precast concrete structure. The reliability of the connection depends on the bond strength between the steel bars and the grouting materials. In this study, the uniaxial tensile test of 204 grouted sleeve connection specimens was carried out. The test parameters included steel bar diameter, steel bar anchorage length, grouting material strength, etc. Test results indicate that there are two main failure modes for the specimens, steel reinforcement tensile fracture and bond failure, which are mainly affected by the anchorage length of steel bars. When the anchorage length is greater than 5ds, the main failure mode is steel bar tension fracture. Furthermore, 236 sets of data in the relevant literatures were collected. Combined with the experimental data, a database of bond strength between steel bars and grouting materials containing 334 sets of data was established, and a calculation formula of ultimate bond strength of grouted sleeve with high applicability was proposed. Finally, the reliability of the grouted sleeve connection with different anchorage lengths and the failure probability under different anchorage lengths were analyzed. On this basis, the minimum anchorage length for different types of steel bars was proposed. The minimum anchorage length of HRB400 steel bars ranges from 5ds to 8ds, the minimum anchorage length of HRB500 steel bars ranges from 7ds to 10ds, and the minimum anchorage length of HRB600 steel bar ranges from 9ds to 12ds.